1418 Nutritional Surveillance in Overweight/Obese Coeliac Children (OCC). (October 2012) - Mercurio, R; Guttadoro, D; Piedimonte, A; Mosca, A; Petrarca, L; Barbato, M; Giacomini, A; Vania, A
Abstract : Background and Aims: Gluten-free-diet (GFD) in Coeliac Disease is often complicated by excessive body weight. This study aims to evaluate the efficacy of a balanced GFD. Methods: Retrospective study. We included OCC followed-up from 2006–2010, with a 1 year follow-up after the diagnosis. For all we assessed weight, height, BMI and z-BMI at diagnosis and 1 year later. We also investigated the compliance with the prescribed food program and GFD, then selecting only patients with strict adherence to GFD, and subdividing them into 2 groups: A (balanced diet) and B (non-controlled diet). Results: The characteristics of A and B, as in Tab.1, show a reduction of z-BMI (Δz-BMI= –0.49±0.41) in all patients of group A, while in group B (Δz-BMI= –0.28±0.54) the z-BMI increased in 2 cases and reduced in 6, but less than in A. Conclusions: Probably due to the small number of cases, the differences in the z-BMI changes between OCC with a balanced GFD and those with a non-controlled GFD are not significant. Nonetheless, we assert that is fundamental that these patients follow ad adequate diet, especially to avoid the worsening of a state of malnutrition in excess, often already present at the diagnosis.